2014
DOI: 10.6007/ijarped/v3-i3/949
|View full text |Cite
|
Sign up to set email alerts
|

Student Voice in Curriculum Change: A Theoretical Reasoning

Abstract: Views about the place of young people in schools and society have changed over the past few years. A major theme in the theoretical framework of constructivist learning is that learning is an active process in which learners connect new knowledge and skills to existing ones and, thus, construct new ideas or concepts based upon their current and past knowledge. In this review, we argue that students' involvement provides opportunities for them to become active participants in their education, including making d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…Lee (1999) adds that "when the voices of students are routinely unsolicited or ignored amid reform planning and implementation, the directions assumed by teachers and administrators can be misguided" (p. 215). Ngussa and Makewa (2014) have theorized that students acquire specific knowledge through the teaching and learning process that provides them the capability to participate in the curricular change process. In a study we conducted, for example, to assess the implementation of a One-to-One Computer Initiative in an urban middle school, we found that students were able to provide valuable insights into the impact of that initiative on their learning and overall school experience (Storz & Hoffman, 2013).…”
Section: A Focus On Student Voicementioning
confidence: 99%
“…Lee (1999) adds that "when the voices of students are routinely unsolicited or ignored amid reform planning and implementation, the directions assumed by teachers and administrators can be misguided" (p. 215). Ngussa and Makewa (2014) have theorized that students acquire specific knowledge through the teaching and learning process that provides them the capability to participate in the curricular change process. In a study we conducted, for example, to assess the implementation of a One-to-One Computer Initiative in an urban middle school, we found that students were able to provide valuable insights into the impact of that initiative on their learning and overall school experience (Storz & Hoffman, 2013).…”
Section: A Focus On Student Voicementioning
confidence: 99%
“…Studies focusing on student voice also refer to student empowerment. In these studies, (Brooker & MacDonald, 1999;Cook-Sather, 2006;Mitra, 2003;Ngussa & Makewa, 2014), student voice does not only refer to students' expressing their views, but also their taking active role in curriculum decisions and evaluation, and having the power to drive change. On the opposite side of student empowerment stands student alienation.…”
Section: Student Empowermentmentioning
confidence: 99%
“…Course instructors in higher education should involve students in the curriculum development process so that they contribute to what they learn. Ngussa and Makewa (2014) state that the student's voice should be heard in the curriculum development process. Students should be empowered to make critical decisions on what they learn, how they learn, and how they are assessed.…”
Section: Promoting Learning How To Learnmentioning
confidence: 99%